Política de financiamento público da educação no município de Barcarena-PA, no período de 2009 a 2016 - RODRIGUES, Luis do Socorro Tavares (2019)
The financing of education constitutes a fundamental factor for the formulation, implementation and evaluation of educational policies, in addition to the programs and related actions. In fact, quality education and appreciation of teachers' professionals depends on the availability of resources to materialize. This work of course conclusion proposed to analyze the financing of education in the municipality of Barcarena / PA in the period from 2009 to 2016. First, the sources of these resources were analyzed, being explicit that the largest share comes from the percentage over taxes, plus of the salary of education and, in collaboration, of the programs of the National Fund for the Development of Education (FNDE). The revenues of both the constitutionally transferred resources and those of the own resources were analyzed, as well as the resources of FUNDEB. Likewise, educational expenses were considered in order to verify if at least 60% of FUNDEB were used for the payment of teaching professionals, and a maximum of 40% were used for the maintenance and development of teaching. The expenses with the National Program of Support to School Transportation (PNATE) were also verified; the National School Lunch Support Program (PNAE) and Direct Money in School (PDDE). It was verified the amount of resources that the education function made available during the period studied and where they were invested. It was evident that the greatest contribution of resources to education comes from FUNDEB, which in the period studied represented, on average, 85.65% of the resources. On the other hand, the own resources presented indexes of 15.40%, which shows the dependence that the municipality has of the resources transferred. The methodology used was documental analysis and research on official websites.